Congenital Deficiency of Vitamin K Dependent Coagulation Factors in Two Families Presents as a Genetic Defect of the Vitamin K-Epoxide-Reductase-Complex - Oldenburg, J.; von Brederlow, B.; Fregin, A.; Rost, S.; Wolz, W.; Eberl, W.; Eber, S.; Lenz, E.; Schwaab, R.; Brackmann, H. H.; Effenberger, W.; Harbrecht, U.; Schurgers, L. J.; Vermeer, C.; Müller, C. R. (Thrombosis and Haemostasis, 2000)
Hereditary combined deficiency of the vitamin K dependent coagulation factors is a rare bleeding disorder. To date, only eleven families have been reported in the literature. The phenotype varies considerably with respect to bleeding tendency, response to vitamin K substitution and the presence of skeletal abnormalities, suggesting genetic heterogeneity. In only two of the reported families the cause of the disease has been elucidated as either a defect in the γ-carboxylase enzyme (1) or in a protein of the vitamin K 2,3-epoxide reductase (VKOR) complex (2).Here we present a detailed phenotypic description of two new families with an autosomal recessive deficiency of all vitamin K dependent coagulation factors. In both families offspring had experienced severe or even fatal perinatal intracerebral haemorrhage. The affected children exhibit a mild deficiency of the vitamin K dependent coagulation factors that could be completely corrected by oral substitution of vitamin K.Sequencing and haplotype analysis excluded a defect within the γ-carboxylase gene. The finding of highly increased amounts of vitamin K epoxide in all affected members of both families indicated a defect in a protein of the VKOR-multienzyme-complex. Further genetic analysis of such families will provide the basis for a more detailed understanding of the structure-function relation of the enzymes involved in vitamin K metabolism.
Keywords: Hereditary bleeding disorder; γ-carboxylation; vitamin K epoxidase-reductase